Lokal ileri evre nazofarenks kanseri tanısı ile primer kemoradyoterapi uygulanmış hastalarda tedaviye bağlı geç dönem toksisitenin değerlendirilmesi, dozimetrik analizi ve yaşam kalitesine etkisi - Kefeli, Ayşegül Üçüncü (My University, 2014)
Bu çalışmada, nazofarenks kanseri tanısı ile kemoradyoterapi uygulanmış hastalarda geç yan etkilerin değerlendirmesi ve yaşam kalitesine etkisinin incelenmesi amaçlandı. Ocak 2004-Mart 2012 tarihleri arasında Marmara Üniversitesi Hastanesi Radyasyon Onkolojisi nda tedavi görmüş 50 hasta geriye dönük olarak incelendi. Hastalardan poliklinik takipleri sırasında şikâyeti ve semptomu nedeniyle incelenmiş olan 27 hasta çalışmaya alındı. Hastalar Hastane Anksiyete ve Depresyon Ölçeğini (HAD), EORTC C-30, HN-35 ölçeklerini ve ağız kuruluğu değerlendirme anketlerini doldurdu. Anket sonuçları dosyalardan elde edilen muayene verileri ve tüm tetkik sonuçları ışığında değerlendirildi. Üç boyutlu tedavi planlama sisteminde ilgili organlara ait yeniden konturlama ve doz hesapları yapıldı. Bu sonuçlar dosyadan alınan verilerle karşılaştırılarak analiz edildi. Buna göre, ortanca takip süresi 61 ay (aralık, 18-11 ay) idi. Nazofarenks ve primer kitleye uygulanan medyan eksternal RT dozu 70 Gy (aralık, 61-73 Gy) idi. Grup ortalamaları anksiyete için 4 (aralık, 0-18) ve depresyon için 2.2 (aralık, 0-11) idi. EORTC QLQ C-30 anketinde hastaların genel sağlık durumu ortalama skoru 78.1 olarak hesaplandı. Fonksiyonel ölçekte uğraşı fonksiyonu en yüksek puanı alırken, semptom ölçeğinde yorgunluk, dispne, iştah kaybı ve mali zorluklar en yüksek puanı aldı. EORTC HN 35 semptom ölçeğinde ise en yüksek puanı ağız kuruluğu, tükrük yapışkanlığı ve ağız açıklığı aldı. On altı (%59.3) hastada hipotiroidi, 11 (%40.7) hastada klinik ve test sonucu işitme kaybı mevcuttu. Baş ağrısı ve baş dönmesi tarif eden üç hastada boyun ultrasonografisinde karotis stenozuna ait bulgu vardı. Hastaların %52’sinde trismus mevcuttu. Bu hastaların doz-volüm histogramlarında temporomandibular eklemin aldığı ortalama doz 60.7 Gy idi. İki hastada brakiyal pleksus tutulumu vardı. Hastaların %89’unda fleksiyon ve ekstansiyon hareketlerinde kısıtlılık olmuştu. Bu hareketlerden sorumlu kasların maksimum dozları 60 Gy ve üzeri, ortalama dozları ise ekstansör kaslar hariç diğer kas gruplarında 40 Gy’in üzerindeydi. Nazofarenks kanseri, radyoterapi, brakiyal pleksus, geç yan etkiler

This study aims to determine the late effects of radiotherapy and its relationship between quality of life who were diagnosed with nasopharyngeal cancer and undergone radiation therapy for head and neck region. Between January2004 and March2012, 50 patients, who were followed in the Marmara University Hospital Department of Radiation Oncology and received primary chemoradiotherapy for locally advanced nasopharyngeal cancer were evaluated retrospectively. Twenty nine patients were invited who were examined regularly in outpatient follow-up. Of these, informed written consents were obtained from 27 who agreed to complete the questionnaires and enrolled into the study. Accordingly, patients were asked to fill out the Hospital Anxiety and Depression Scale (HADS), EORTC QLQ C-30, H N-35 scales and dry mouth evaluation questionnaires. Re-contouring and dose calculations of the related organs have been done with three-dimensional treatment planning system. These results were analyzed and compared with clinical records. The mean follow-up was 61 months (range, 18-11 months). The median external RT dose applied to the nasopharynx and primary tumor was 70 Gy (range, 61-73 Gy). Twenty six (%96) patients received concurrent chemotherapy. Median scores of the groups were 4 (range, 0-18) for anxiety and 2.2 (range, 0-11) for depression, respectively. General health status median scores of patients in the EORTC QLQ C-30 test was calculated as 78.1. The highest score on the functional scale was the physical functoning , while the fatigue, dyspnea, loss of appetite and financial difficulties received the highest score in symptom scale respectively. Dry mouth, saliva stickness and mouth opening received the highest score in the EORTC H&N 35 symptom scale. Hypothyroidism was determined in 16 (59.3%) patients in the late toxicity assessment. Findings related to the carotid stenosis were found in the neck ultrasonoghraphy in 3 patients who were complaining of headache and dizziness. Hearing loss was determined clinically and by hearing test in eleven (40.7%) patients. None of the patients had vision loss clinically. The median dose of the temporomandibular joint of these patients was 60.7 Gy in the dose-volume histograms. Two out of 25 patients were affected with brachial plexopathy in the electroneuromyography (ENMG). Based on the evaluation of patients with cervical spine range of motion, 88.9% in the flexion and rotation movements, 77.8% in the extension, 88.9% in the right lateral flexion and 85.2% of cases in the left lateral flexion were restricted. Maximum doses of the mucles that are responsible for these movements were 60 Gy and above and median doses of other muscles except from extensor muscles were greater than 40 Gy. Nasopharyngeal cancer, radiotherapy, brachial plexus, late effects
Keywords: Kanser